Aplikasi Multimedia Interaktif Pengenalan Pahlawan Nasional (Studi Kasus: SD Swasta Daan Mogot 1 Keroncong Kota Tangerang) - Sigit Sigit; Belsana Butar Butar (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - The conventional teaching and learning process for most students is very boring, because only listening to the explanation from the teacher and also using the textbook as a reference for learning so that when students learn less attention to the material delivered. To overcome this, an interactive application was made about learning the introduction of Indonesian national heroes. The use of interactive animation as a visual media will make it easier for teachers to deliver material about national heroes and make it easier for students to remember national heroes as well as their history. Multimedia applications are applications that are designed and built by combining elements such as text/documents, sounds, images, animations and videos. With the use of multimedia, learning about national heroes can be more interactive, increasing students' motivation during the learning process until the desired learning goals are obtained. Before making the application using Adobe Flash Professional CS6 software (Action Script 2.0), storyboard design was used in the form of a picture in the form of a box as the main guide in making animation. From the discussions and questionnaires that have been disseminated, this animation is useful to help and facilitate teachers and parents to be able to introduce national heroes and also develop the mindset of early-level Daan Mogot 1 Keroncong Elementary School Tangerang City level five and create an atmosphere of learning while playing interesting for children. Key words: Multimedia, Learning National Hero, Animation, Storyboard